Role of lncRNAs in the pathogenic mechanism of human decreased ovarian reserve - Lv, Zhexi; Lv, Zekai; Song, Linjiang; Zhang, Qinxiu; Zhu, Shaomi (Frontiers in Genetics, 2023)
Decreased ovarian reserve (DOR) is defined as a decrease in the quality and quantity of oocytes, which reduces ovarian endocrine function and female fertility. The impaired follicular development and accelerated follicle atresia lead to a decrease in the number of follicles, while the decline of oocyte quality is related to the disorder of DNA damage-repair, oxidative stress, and the dysfunction of mitochondria. Although the mechanism of DOR is still unclear, recent studies have found that long non-coding RNA (lncRNA) as a group of functional RNA molecules participate in the regulation of ovarian function, especially in the differentiation, proliferation and apoptosis of granulosa cells in the ovary. LncRNAs participate in the occurrence of DOR by affecting follicular development and atresia, the synthesis and secretion of ovarian hormones. This review summarizes current research on lncRNAs associated with DOR and reveals the potential underlying mechanisms. The present study suggests that lncRNAs could be considered as prognostic markers and treatment targets for DOR.